THE IMPORTANCE OF DIGITAL COMPETENCIES FOR FUTURE COMPUTER SCIENCE TEACHERS - Mahfuza Zokhidova (Galaxy International Interdisciplinary Research Journal, 2023)
The article discusses the importance of digital competencies for future computer science teachers.